1999
DOI: 10.1093/ndt/14.8.1934
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular morbidity and endothelial dysfunction in chronic haemodialysis patients: is homocyst(e)ine the missing link?

Abstract: Hyperhomocyst(e)inaemia is associated with increased cardiovascular risk in haemodialysis patients. Folate supplementation was partially effective in lowering hyperhomocyst(e)inaemia, but its usefulness in terms of reduction in cardiovascular morbidity and mortality remains to be determined in prospective trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
2
4

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 40 publications
1
43
2
4
Order By: Relevance
“…Hyperhomocysteinemia has been shown to be another risk factor for thrombosis and cardiovascular problems, but its specific role in the pathogenesis of thrombotic complications remains unknown [36]. Our results are consistent with these previous findings and suggest that hyperhomocysteinemia may contribute to hypercoagulability in children undergoing dialysis.…”
Section: Discussionsupporting
confidence: 92%
“…Hyperhomocysteinemia has been shown to be another risk factor for thrombosis and cardiovascular problems, but its specific role in the pathogenesis of thrombotic complications remains unknown [36]. Our results are consistent with these previous findings and suggest that hyperhomocysteinemia may contribute to hypercoagulability in children undergoing dialysis.…”
Section: Discussionsupporting
confidence: 92%
“…Evidence to support this assertion also comes from in vitro data, which show that free homocysteine species inactivate NO, promote the generation of oxygen-derived free radicals, induce tissue factor release, and cause endothelial cell injury. 10,12,13,32 Our observations of improved vascular function after B vitamin supplementation in patients with established atherosclerosis are in contrast with previous findings in patients with end-stage renal disease 25 and in animal models of atherosclerosis. 21,33 The lack of improvement in endothelial function despite reduced homocysteine concentrations in these studies may be explained by the failure of folate supplementation to lower plasma homocysteine concentrations Ͻ20 mol/L in patients with end-stage renal disease 25 and the concurrent administration of an atherogenic diet in primates, 21 factors that may have a continuing effect on endothelial function.…”
Section: Chambers Et Al Free Homocysteine and Endothelial Function 2481contrasting
confidence: 99%
“…Studies investigating the effects of lowering homocysteine concentrations on vascular endothelial function have yielded conflicting results. [21][22][23][24][25][26][27] In primates, folate supplementation is reported to reduce plasma homocysteine concentrations but not to affect vascular function. 21 In healthy human subjects, folate supplementation is associated with reduced homocysteine concentrations and improved vascular endothelial function, 22,23,26 although in these studies, there was no relationship between homocysteine concentrations and endothelial function, implying that the effects of B vitamins on endothelial function may not be mediated through homocysteine lowering.…”
mentioning
confidence: 99%
“…It has been proposed that this high prevalence of hyperhomocysteinemia in dialysis patients is one of the main reasons for the high rate of cardiovascular events and poor clinical outcome in these individuals (5-9). Although some studies reported positive correlations between increased tHcy and higher rate of mortality in dialysis patients (7)(8)(9), other studies failed to show such an association (39,40) or found paradoxically reversed correlations (10 -12). Sirrs et al (10) examined the association between tHcy and vascular access complications in 96 MHD patients and did not find any correlation between them.…”
Section: Discussionmentioning
confidence: 99%